2012
DOI: 10.1029/2012jb009201
|View full text |Cite
|
Sign up to set email alerts
|

Seismic characterization of hydrates in faulted, fine‐grained sediments of Krishna‐Godavari Basin: Full waveform inversion

Abstract: [1] In fine-grained, faulted sediments, both stratigraphic and fault-induced structural variations can simultaneously determine the gas hydrate distribution. Insights into hydrate distribution can be obtained from P wave velocity (V P ) and attenuation (Q P À1 ) character of the gas hydrate stability zone (GHSZ). In this paper, we apply frequency domain full-waveform inversion (FWI) to surface-towed 2D multichannel seismic data from the Krishna-Godavari (KG) Basin, India, to image the fine-scale (100 Â 30 m) V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 83 publications
(78 reference statements)
1
16
0
Order By: Relevance
“…This resolution can be significantly improved by applying full waveform inversion to the OBS data (Minshull & Singh, ; Singh et al, ; Westbrook et al, ; Xia et al, ). Depending on the type and the quality of the data set, several 1‐D (Korenaga et al, ; Pecher et al, ; Westbrook et al, ; Xia et al, ) and 2‐D full waveform inversion (Delescluse et al, ; Jaiswal et al, ; Wang et al, ) approaches have been used in the past to study the distribution of gas hydrates. In this study, OBS stations are not spaced closely enough to have overlap of raypaths in layers below the seafloor; hence, 1‐D full waveform inversion is more suitable for this data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resolution can be significantly improved by applying full waveform inversion to the OBS data (Minshull & Singh, ; Singh et al, ; Westbrook et al, ; Xia et al, ). Depending on the type and the quality of the data set, several 1‐D (Korenaga et al, ; Pecher et al, ; Westbrook et al, ; Xia et al, ) and 2‐D full waveform inversion (Delescluse et al, ; Jaiswal et al, ; Wang et al, ) approaches have been used in the past to study the distribution of gas hydrates. In this study, OBS stations are not spaced closely enough to have overlap of raypaths in layers below the seafloor; hence, 1‐D full waveform inversion is more suitable for this data set.…”
Section: Methodsmentioning
confidence: 99%
“…A BSR only provides evidence for the presence of gas hydrates but does not allow for estimation of the amount of gas hydrates trapped in sediments. Gas hydrates fill pore space by forming a sediment‐hydrate microstructure strengthening the matrix of unconsolidated sediments that in turn increases the bulk modulus, thereby resulting in higher P wave seismic velocities compared to sediments not saturated with gas hydrates (Bünz et al, ; Chand et al, ; Helgerud et al, ; Jaiswal et al, ; Lee et al, ; Lee & Collett, ; Lu & McMechan, ; Stoll et al, ; Yuan et al, ). Hence, high P wave seismic velocities are observed above the BSR, whereas the presence of free gas in sediments below the BSR reduces the P wave velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Because gas hydrate increases the stiffness of the matrix (Jung et al, 2012) and P-wave velocity, it was normally assumed that the sediments saturated with gas hydrates will show lower attenuation (Wood et al, 2000). Unlike P-wave velocity, no unique trend of seismic attenuation in gas hydrates can be observed from the literature; thus, making attenuation characteristic of the gas hydrate bearing sediments a debatable topic (Guerin et al, 1999;Wood et al, 2000;Chand et al, 2004;Rossi et al, 2007;Sain et al, 2009;Sain and Singh, 2011;Jaiswal et al, 2012;Dewangan et al, 2014). Laboratory experiments in hydrate bearing sediments indicated increase of attenuation with hydrate saturation (Priest et al, 2006;Best et al, 2013), whereas attenuation estimates from field experiments on gas hydrates indicated contradicting results.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated hydrate concentration and the gas saturation for these CDPs are close to 20% and 10%, respectively. Interestingly, the velocity model obtained using unified imaging and waveform inversion [ Jaiswal et al ., , ] confirms the presence of free gas in the vicinity of CDP 450.…”
Section: Discussionmentioning
confidence: 98%
“…Anisotropy Due to Fracture-Filled Gas Hydrate [21] The distribution of gas hydrates is often governed by lithology; for example, they get preferentially deposited in the sandy layers at the Mallik site [Dallimore et al, 1999] and in the Nankai trough [Matsumoto et al, 2001] and within the coarse ash-layers in the Andaman basin [Collett et al, 2008]. The gas hydrate accumulation may also be governed by structure controls; for example, hydrate gets preferentially deposited in the fault/fracture network in the KG offshore basin [Collett et al, 2008;Dewangan et al, 2011;Jaiswal et al, 2012aJaiswal et al, , 2012b. Such fracture-filled deposits may exhibit significant lateral heterogeneity.…”
Section: Ava Pattern Of Bsr Using Tpbe Modelmentioning
confidence: 99%